The Importance of BPJS Management as a Means of Community Admisntation - Laili Wulandari; Candra Jaya (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Bpjs is a social institution formed for the welfare of the people in Indonesia. However, there are two existing BPJS, namely Bpjs in terms of employment and also Bpjs in terms of health. Indeed, it is given by the government for the welfare of the community but still the payment facility for payment is no later than 15 (fifteen) days since the documents from the claim received are complete. Programs carried out by the government to the community with the help of Bpjs must be with the flow and procedure of services, the correct population, as well as with the existing population census, for example, such as health Bpjs